2021
DOI: 10.3390/jcm10030497
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor-Like Weak Inducer of Apoptosis and Selected Cytokines—Potential Biomarkers in Children with Solitary Functioning Kidney

Abstract: This study was performed to explore serum tumor necrosis factor-like weak inducer of apoptosis (TWEAK) and its dependent cytokines urinary excretion: monocyte chemoattractant protein-1 (MCP-1) and regulated on activation, normal T cell expressed and secreted chemokine (RANTES) with their relation to the kidney function parameters in children with solitary functioning kidney (SFK). The study included 80 children and adolescents (median age 9.75 year) with congenital and acquired (after surgical removal) SFK. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
1
1
Order By: Relevance
“…In our analysis, the prevalence of hypertension was 8.8%, while in previous studies in children with SFK, the number of hypertensive patients ranged from 13 to 26% [ 25 , 35 ]. In the KIMONO study by Westland et al, the authors concluded that an SFK from childhood implies a substantial risk for hypertension [ 20 ].…”
Section: Discussioncontrasting
confidence: 56%
“…In our analysis, the prevalence of hypertension was 8.8%, while in previous studies in children with SFK, the number of hypertensive patients ranged from 13 to 26% [ 25 , 35 ]. In the KIMONO study by Westland et al, the authors concluded that an SFK from childhood implies a substantial risk for hypertension [ 20 ].…”
Section: Discussioncontrasting
confidence: 56%
“…It may be detected by using the antibody M30. Cleavage of various caspases can be detected using flow cytometry during apoptosis [28,29]. The widely used biomarkers of apoptosis, their methods of analysis and the specimen needed for analysis are discussed in Table 2.…”
Section: Bio Markers Of Apoptosismentioning
confidence: 99%